Clinical study of falls among inpatients with hematological diseases and exploration of risk prediction models - Wang, Jing; Chen, Bin; Xu, Fang; Chen, Qin; Yue, Jing; Wen, Jingjing; Zhao, Fang; Gou, Min; Zhang, Ya (Frontiers in Public Health, 2023)
Background: Falls are serious health events that can cause life-threatening injuries especially among specific populations. This study assessed the risk factors associated with falls among inpatients with hematological diseases and explored the predictive value of fall risk assessment models. Methods: Clinical data from 275 eligible hematology disease patients who were seen at Mianyang Central Hospital with or without falls from September 2019 to August 2022 were retrospectively analyzed. Fall risk scores were determined in all included patients. Clinical characteristics were compared between patients with and without falls. Binary logistic regression models were used to screen for potential fall-specific risk factors among hospitalized patients with hematology diseases. Results: Fall occurred in 79 cases. Patients in the fall group had a higher CCI, a higher incidence of diabetes mellitus, visual impairment, hematological malignancies, and maintenance of stable disease stage, higher glucose levels, and a greater proportion of dizziness, nocturnal defecation and receipt of intensive chemotherapy than those in the non-fall group (all P <0.05). Fall patients were also more likely to have used diuretics, laxatives, sedative-sleeping drugs, analgesics, albumin, and calcium, and to have had catheters placed. The Barthel Index, grade of nursing care, support of chaperones, body temperature, nutrition score, and pain score also differed significantly between the two groups (all P <0.05). Multivariable logistic regression analysis showed that the maintenance of stable disease stage (P <0.001), use of sedative and sleeping drugs ( P=0.038), use of diuretics ( P <0.001), and intensive chemotherapy (P <0.001) were independent risk factors for falls. A high Barthel Index ( P <0.001), a high level of nursing care (P=0.047), and availability of family accompaniment ( P <0.001) were protective factors for falls. ROC curve analysis was used to evaluate the predictive value of different fall-specific risk scales among inpatients with hematological diseases. The Johns Hopkins Fall Risk Rating Scale had high sensibility and specificity with an area under the curve of 0.73 (P <0.001). Conclusion: The JHFRAT had a strong predictive value for falls among hospitalized patients with hematology diseases and can be recommended as a valid tool for clinical use.